DAKWAH MODERAT: KAJIAN KONSEPTUAL - Alawiyah, Elpi (Dirasa Islamiyya: Journal of Islamic Studies, 2023)
Da'wah studies in Islamic thought have been widely studied. In fact, in the context of science development, UIN or IAIN already have many da'wah faculties with various study programs offered. Related to the development of knowledge, da'wah has a dimension of thought. This study used a qualitative approach. The method was literature study. Data collection technique is done by content analysis. The literature sources were selected and directed at several literatures related to moderate preaching. The researcher choosed, selected, recorded, and described the results of the analysis according to the theme being studied. The preaching that is expected is not forcing someone. Da’wah is inviting as well as inviting in realizing the principles of kindness and peace among others. In this case moderate preaching needs to be shown especially in the context of today's religious life. The concept of moderate preaching is in accordance with the characteristics of religious moderation which is the priority program of the Ministry of Religion. With religious moderation, preaching is encouraged with nuances that are tolerant, balanced and fair. Thus, da'wah can be a process and a way to present messages of goodness that unite in the peace of others.